Implementation of Cyber Public Relations by Digmo Agency to Increase Mimume Brand Awareness Through the Instagram Platform - Aqila Devina, Fadia; Syahradinar Lukman, Alifia; Aprilia, Indah (PT Literasi Nusantara Publisher, 2023)
Public Relations is a management function that builds on maintaining good and beneficial relationships for the organization with its publics in influencing the success or failure of the organization. The function of Public Relations is to provide information to the public, carry out persuasion which aims to change the attitudes and actions of the community directly and to integrate the attitudes and actions of the community or vice versa. Along with the development of technology, Public Relations is required to be able to operate the company's social media in order to get a positive image and an appropriate target market and establish good relations with the company's public as well as increase social media engagement and increase public awareness of the company. MiMuMe is a business engaged in the culinary field during the COVID-19 pandemic, to increase brand awareness and get the right target market, MiMuMe uses the services of Digmo Agency to increase MiMuMe's Instagram engagement. Digmo Agency implements cyber public relations activities with the aim of making it easier to develop content creation strategies and find out what the MiMuMe target market likes. This study aims to find out what cyber public relations activities are carried out by Digmo Agency to increase brand awareness of its clients, namely MiMuMe, and the results of these activities.